2016
DOI: 10.1016/j.procs.2016.07.414
|View full text |Cite
|
Sign up to set email alerts
|

Psychologically Inspired Planning Method for Smart Relocation Task

Abstract: Behavior planning is known to be one of the basic cognitive functions, which is essential for any cognitive architecture of any control system used in robotics. At the same time most of the widespread planning algorithms employed in those systems are developed using only approaches and models of Artificial Intelligence and don't take into account numerous results of cognitive experiments. As a result, there is a strong need for novel methods of behavior planning suitable for modern cognitive architectures aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Since the learning speed is low only using the ANNs, and it is impossible to learn all the states only using the Q-learning algorithm, we can combine them to overcome the disadvantages of either [133]. In general, there are five outputs for AGVs in warehouses, i.e., travel forward, stop, turn left 90°, turn right 90°and self-rotate 180° [13], Demircan et al [134] used ANNs to create route-planning controllers and then used Q-learning algorithm to collect training data for ANNs.…”
Section: (D) Anns Combined With Q-learning Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the learning speed is low only using the ANNs, and it is impossible to learn all the states only using the Q-learning algorithm, we can combine them to overcome the disadvantages of either [133]. In general, there are five outputs for AGVs in warehouses, i.e., travel forward, stop, turn left 90°, turn right 90°and self-rotate 180° [13], Demircan et al [134] used ANNs to create route-planning controllers and then used Q-learning algorithm to collect training data for ANNs.…”
Section: (D) Anns Combined With Q-learning Algorithmmentioning
confidence: 99%
“…Deep Q-Networks (DQN) is generated by combining the ANNs and the Q-learning algorithms. The preliminary studies of employing the DQN in AGVs route planning on square grids world, showed that the DQN can perform robustly on square grids world [133,136,137].…”
Section: (D) Anns Combined With Q-learning Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of creating AGI systems, the DSN algorithm can be used to automatically generate scripts for the behavior of an intelligent agent. These scripts can be used to speed up the agent's own behavior planning process [9,7], or to predict user behavior in a cognitive assistant scenario [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to integration of task and motion planning [6], but unlike other researchers in this field we do not concentrate on task planning with grasping the objects, which is a typical scenario, but rather on task planning with path finding. The approach we suggest can be of particular interest to solving so-called smart relocation tasks [11], [12] when the mission can not be accomplished without the robots helping each other.…”
Section: Introductionmentioning
confidence: 99%